2013
DOI: 10.2340/00015555-1597
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Immunosuppressive and Immunomodulatory Cells in Keratoacanthoma and Cutaneous Squamous Cell Carcinoma

Abstract: An imbalance of immunosuppressive and immunomodulatory cells plays an important role in inhibiting the anti-tumour immune response in a tumour-bearing host. Among such cells, regulatory T cells (Tregs), together with immunosuppressive macrophages, such as CD163+ M2 macrophages, play roles in maintaining the tumour microenvironment. In contrast, interleukin-27 (IL-27) induces STAT1 and STAT3 activation, thus resulting in the enhancement of naive CD4 T-cell proliferation, the promotion of early Th1 differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 35 publications
6
45
0
Order By: Relevance
“…7,47,48 There are several reports of differential expression of molecular markers, such as laminin-32, nuclear factor kappa B/p50, cortactin, glut-1, Bcl-x, beta-catenin, CD44, anti-P2 X7, K10, E-cadherin, transforming growth factor-a, peanut agglutinin, peanut lectin receptor, and carcinoembryonic antigen, in KAs and SCCs. 22,31,40,43,44,[49][50][51][52][53][54][55][56][57][58][59][60][61][62] KAs were consistently positive for K6, K10, and K14. K10 and K14 were observed in specialized cells within the ORS of the hair follicle and in the interfollicular epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…7,47,48 There are several reports of differential expression of molecular markers, such as laminin-32, nuclear factor kappa B/p50, cortactin, glut-1, Bcl-x, beta-catenin, CD44, anti-P2 X7, K10, E-cadherin, transforming growth factor-a, peanut agglutinin, peanut lectin receptor, and carcinoembryonic antigen, in KAs and SCCs. 22,31,40,43,44,[49][50][51][52][53][54][55][56][57][58][59][60][61][62] KAs were consistently positive for K6, K10, and K14. K10 and K14 were observed in specialized cells within the ORS of the hair follicle and in the interfollicular epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…Regulation of ABCA1 expression impacts the reverse cholesterol transport (RCT) and foam cell formation [13][14][15]. In detail, IL-27 activates cellular signal pathway [16][17][18][19], and induction of anti-inflammatory immune responses [7,20]. Several studies reported a potential role of STAT molecules in the ABCA1 gene regulation [21,22].…”
Section: Introductionmentioning
confidence: 98%
“…Before the antigen retrieval procedure, we used 0.3% H 2 O 2 in methanol to inhibit endogenous peroxidase. The 10 cutaneous BP and PV samples were processed for single staining of IL-4, IL-13, pSTAT6, pSTAT1, CD163, CD206, CCL17, CCL18 and Foxp3, and developed with liquid permanent red (Dako A/S, Glostrup, Denmark) or with 3,3′-diaminobenzidine tetrahydrochloride (Wako Pure Chemical Industries, Osaka, Japan) as we previously reported [11]. …”
Section: Methodsmentioning
confidence: 99%